PENGEMBANGAN MEDIA PAPAN KADOBUDI (KARTU DOMINO BUDAYA JAWA TIMUR) PADA MATERI KERAGAMAN BUDAYA PADA SISWA KELAS IV SDN 2 PICISAN - Intan Khoirun Nisa; Ilmawati Fahmi Imron; Aan Nurfahrudianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by observations at SDN 2 Picisan, which revealed low learning outcomes among fourth-grade students on the topic of cultural diversity in East Java. This issue is attributed to the lack of optimal use of instructional media and the dominance of monotonous lecture methods. To address this problem, the study formulates the following research questions.1. How valid is the KADOBUDI Board media for Social Studies learning content on East Java cultural diversity for fourth-grade students?, 2. How practical is the KADOBUDI Board media for Social Studies learning content on East Java cultural diversity for fourth-grade students?, 3. How effective is the KADOBUDI Board media for Social Studies learning content on East Java cultural diversity for fourth-grade students?. Using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), this research includes problem identification, media design, product development and validation by subject matter and media experts, as well as limited and broad field trials. Data were analyzed both qualitatively and quantitatively to assess the validity, practicality, and effectiveness of the media. The results show that the KADOBUDI Board media is highly valid (92.33%), highly practical (95%), and effective (87.3%) in improving student learning outcomes, with minor revisions made to image sizing for clarity.